RhlA Converts β-Hydroxyacyl-Acyl Carrier Protein Intermediates in Fatty Acid Synthesis to the β-Hydroxydecanoyl-β-Hydroxydecanoate Component of Rhamnolipids in Pseudomonas aeruginosa - Zhu, Kun (American Society for Microbiology (ASM), 2008)
Pseudomonas aeruginosa secretes a rhamnolipid (RL) surfactant that functions in hydrophobic nutrient uptake, swarming motility, and pathogenesis. We show that RhlA supplies the acyl moieties for RL biosynthesis by competing with the enzymes of the type II fatty acid synthase (FASII) cycle for the β-hydroxyacyl-acyl carrier protein (ACP) pathway intermediates. Purified RhlA forms one molecule of β-hydroxydecanoyl-β-hydroxydecanoate from two molecules of β-hydroxydecanoyl-ACP and is the only enzyme required to generate the lipid component of RL. The acyl groups in RL are primarily β-hydroxydecanoyl, and in vitro, RhlA has a greater affinity for 10-carbon substrates, illustrating that RhlA functions as a molecular ruler that selectively extracts 10-carbon intermediates from FASII. Eliminating either FabA or FabI activity in P. aeruginosa increases RL production, illustrating that slowing down FASII allows RhlA to more-effectively compete for β-hydroxydecanoyl-ACP. In Escherichia coli, the rate of fatty acid synthesis increases 1.3-fold when RhlA is expressed, to ensure the continued formation of fatty acids destined for membrane phospholipid even though 24% of the carbon entering FASII is diverted to RL synthesis. Previous studies have placed a ketoreductase, called RhlG, before RhlA in the RL biosynthetic pathway; however, our experiments show that RhlG has no role in RL biosynthesis. We conclude that RhlA is necessary and sufficient to form the acyl moiety of RL and that the flux of carbon through FASII accelerates to support RL production and maintain a supply of acyl chains for phospholipid synthesis.